FORMULASI DAN UJI SIFAT FISIK LILIN AROMATERAPI KOMBINASI ROSEMARY (ROSMARINUS OFFICINALIS L.) DAN DAUN MINT (MENTHA ARVENSIS) - Tulak Rerung, Lola'; Oktaviani, Milla (Politeknik Tiara Bunda, 2023)
Essential oils have a distinctive aroma and are volatile. In general, essential oils are used as food flavoring, perfume, cosmetics, aromatherapy and medicine. Rosemary (Rosmarinus Officinalis L.) contains essential oils with the main ingredients being 1,8-cineol, camphor, α-pinene limonene, camphene and linalool which are useful for reducing anxiety and improving memory. Mint leaves (Mentha arvensis) contain menthol which is antiseptic, carminative, cooling, stimulant, diuretic and has a sedative and relaxing effect. This research was conducted to formulate and test the physical properties of a combination of Rosemary (Rosmarinus officinalis L.) and Mint (Mentha arvensis) aromatherapy candles. This research method was experimental with the formulas F1 (1%:1%), F2 (3%:3%), and F3 (5%:5%), then organoleptic tests, burning time tests, and preference tests were carried out. The results showed that all formulas had a distinctive aromatic shape, color, and smell. F2 preparation wax has the longest burning time. The results of the preference test showed that the F2 wax preparation was much liked by the respondents.